“Say Cheese”: family photos, modern Malay masculinity and family narrative in some Malaysian films - Jamaluddin Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Family photographs are often used as a prop in a set-up of a family home in a film. Employing visual culture approach, I would argue that through the use of family portraits both in figurative and artefactual forms, the narrative about family is often unravelled, challenged and subsequently validated. A close textual analysis of three P. Ramlee’s films that mark the dawn of modernism in the immediate post-independence Malaya and the formation of Malaysia in 1963 as a case study, this paper asks the following questions: What types of narratives are created through the display of family portraits? How do these family portraits reflect the changing conceptions of the institution of the family especially pertaining to modern Malay masculinity? And, how do family photographs inform family narratives? The analysis finds that, on one hand, family portraits are used to narrate the exteriorization of masculinity in trouble by revealing its castration anxiety. On the other, they also point to “the hero journey archetype” that apotheosizes masculine dominance as proven by the films’ happy ending. The implication of this study lies in the way family photographs in films can be understood not merely as props, but in visual culture sense, as locating the source of the conflict of modern Malay masculinity in the family itself. Although family portraits in these films are meant to be innocuous to Malay masculinity in crisis, it is ideologically a folie de grandeur about the family and what it means for the nation in transition.